Comparative Efficacy of 3 Adjuvant Medications Used in Combination with Intrathecal Bupivacaine for Caesarian Section Anesthesia: A Randomized, Double-Blind Clinical Trial - Reza Jouybar, MD; Zeinabsadat Fattahi Saravi, MD; Nazi Dehghani, MD; Sara Sadeghi, MD; Sahar Chehelgerdi Samani, MD; Zahra Esmaeilinezhad, MSc; Farzaneh Masihi, MSc; Naeimehosadat Asmarian, PhD (Elsevier, 2022)
ABSTRACT: Background: A number of different medications are used in combination with intrathecal bupivacaine for cesarean section anesthesia, but their relative efficacy has not been well established. Objective: To study the relative efficacy of adding either intrathecal fentanyl, intrathecal sufentanil, or intravenous acetaminophen-morphine-fentanyl to intrathecal bupivacaine spinal anesthesia for pain control in elective cesarean section operations. Methods: In this randomized, double-blinded, controlled trial, 105 pregnant women eligible for cesarean section received 10 mg intrathecal bupivacaine (0.5%) in combination with 2 μg intrathecal sufentanil (group 1), 10 μg intrathecal fentanyl (group 2), and an intravenous cocktail of 1 g acetaminophen, 5 mg morphine, and 100 μg fentanyl (group 3). Patients were assessed for analgesia, time to block, and adverse effects. Results: The 3 groups were similar in terms of the time to onset of sensory block and the duration of both sensory and motor block. Groups 1 and 3 differed significantly in the time to peak sensory block, whereas group 1 differed significantly from groups 2 and 3 in the time to peak motor block. The sensory block level reached T4 in most patients. Significant differences in pain (visual analog scale) were demonstrated between groups 1 and 3 at 5 minutes after spinal injection, between groups 1 and 2 at the end of the surgery and upon arrival to the recovery room, and between all groups in the recovery room. Conclusions: When used in addition to 10 mg intrathecal bupivacaine, an intravenous cocktail of 1 g acetaminophen-5 mg morphine-100 μg fentanyl was as efficient as either 10 μg intrathecal fentanyl or 2 μg intrathecal sufentanil in terms of sensory and motor block duration and produced a higher dermatomal level of sensory block. However, intrathecal sufentanil provided better anesthesia quality (less time to onset of motor block and peak sensory-motor block) and better pain control. (Curr Ther Res Clin Exp. 2023; 84:XXX-XXX)